CD4(+) T cells from mice with intestinal immediate-type hypersensitivity induce airway hyperreactivity - (:unkn) unknown (WILEY, 2007)
A subset of food-allergic patients does not only respond clinically with symptoms in the gastro-intestinal tract but also with asthmatic reactions. The aim of this study was to analyse whether CD4(+) T cells from mice with intestinal immediate-hypersensitivity reactions to food allergen are involved in the development of experimental asthma. BALB/c mice were intraperitoneally sensitized to ovalbumin (OVA), followed by repeated intra-gastric (i.g.) OVA challenges. Control animals were either sham-sensitized or sham-challenged with phosphate-buffered saline (PBS). Duodenum, jejunum, ileum and colon were histologically examined. CD4(+) T cells from mesenteric lymph nodes were transferred from various donor groups into recipient mice that received either OVA or PBS aerosol challenges. Recipients were analysed by measurements of lung function using head-out body-plethysmography and examination of broncho-alveolar lavage and lung histology. The highest levels of OVA-specific IgE antibody levels were detected in OVA-sensitized and OVA-challenged mice. Throughout the lower intestinal tract, a marked infiltration with eosinophils was observed, and goblet cell numbers as well as goblet cell area were significantly increased. The villus/crypt ratio was decreased compared with controls. The transfer of CD4(+) T cells from mesenteric lymph nodes of OVA-sensitized and OVA-challenged mice triggered airway hyperreactivity and eosinophilic airway inflammation in recipients aerosol challenged with OVA, but not with PBS. We conclude that CD4(+) T cells from mesenteric lymph nodes of mice with allergen-induced immediate-type hypersensitivity reactions in the gut are able to transfer the phenotype of experimental asthma.
Keywords: airway hyperreactivity; allergic asthma; CD4(+) T cell transfer; food allergy; FOOD ALLERGY; CHILDREN; HYPERRESPONSIVENESS; LYMPHOCYTES; ASTHMA; EOSINOPHILS; RESPONSES; MANIFESTATIONS; ALPHA-4-BETA-7; INFLAMMATION